ACTUALIZING DISTRIBUTIVE JUSTICE IN DIACONAL MINISTRY THROUGH A DIGITAL THEOLOGY APPROACH USING FUZZY MADM (SAW MODEL) - Theo Pilus Candra (STMIK Indonesia Banda Aceh, 2026)
Diaconal ministry is a mandate for the church to manifest God's love to the vulnerable. However, in practice, aid distribution is often hindered by assessor subjectivity (elders/deacons), nepotism, and data inaccuracy, leading to the kind of injustice seen in the early church (Acts 6:1). This study proposes an interdisciplinary